Perancangan dan Pembuatan Website Pengambilan Ide Skripsi Pada Prodi Teknik Informatika UMY - Kurnianti, Apriliya; Setyawan, Haris; Firdaus, Fathania Firwan; Yuma, Safira Nira (Semesta Teknika, 2018)
In the Kamus Besar Bahasa Indonesia (KBBI), Idea is a design arranged in mind. The thesis idea is a design that can come from thought of student and lecturer. In the Informatics Engineering Department at Muhammadiyah University of Yogyakarta, thesis idea is often offered to student by several lecturers through social networking forums or instant messaging. Thesis ideas was offered through social networking forum or instant messaging can be covered by other content quickly, thus the information was not delivered to students who need a thesis idea optimally . The effect was some students were still confused to get thesis ideas and lecturers who had thesis ideas did not know that there were still students whom needed the idea. To overcome this case, a website-based thesis idea taking system was built to help students to get information and to take thesis ideas which was given by lecturers. In building or repairing a website, Researcher used the waterfall method. Using this method, website development will be more organized. Website development used PHP programming language with CodeIgniter framework. Researcher Tested through three steps, i.e. user interface, functionality and validation testing.